1998
DOI: 10.1177/073346489801700401
|View full text |Cite
|
Sign up to set email alerts
|

Targets, Messages, and Channels for Educational Interventions on Urinary Incontinence

Abstract: This article documents a collaborative health agency-university community demonstration project on urinary incontinence in older women. The basic program-research division of respon sibility was blurred substantially in this collaboration. The article focuses on a telephone survey of 321 elderly women conducted as part of a needs assessment, which also served as baseline data in the evaluation of a public education initiative. The survey provided information for defin ing target populations, shaping educationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…In a general population survey of elderly women, we found that 34% reported some degree of incontinence, and 20% of older women had episodes at least weekly (McFall & Yerkes, 1998). In a general population survey of elderly women, we found that 34% reported some degree of incontinence, and 20% of older women had episodes at least weekly (McFall & Yerkes, 1998).…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…In a general population survey of elderly women, we found that 34% reported some degree of incontinence, and 20% of older women had episodes at least weekly (McFall & Yerkes, 1998). In a general population survey of elderly women, we found that 34% reported some degree of incontinence, and 20% of older women had episodes at least weekly (McFall & Yerkes, 1998).…”
Section: Discussionmentioning
confidence: 64%
“…Several interesting features of this study stem from its public health perspective. In a general population survey of elderly women, we found that 34% reported some degree of incontinence, and 20% of older women had episodes at least weekly (McFall & Yerkes, 1998). Recruitment from nonclinical settings will therefore identify participants with less frequent episodes of incontinence (cf.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only a few of those affected seek professional help. This can be for various reasons: fears of intrusive interference, shame, or the attitude that incontinence belongs to the natural aging process and is not treatable (Dugan et al, 2001;Fall & Yerkes, 1998;Hägglund & Wadensten, 2007;O'Donnell, Lose, Sykes, Voss, & Hunskaar, 2005). There are however a number of treatment options available for sufferers of incontinence.…”
mentioning
confidence: 99%
“…For the remainder of the telephone numbers, the call team was unable to contact 2,316 individuals; 950 were not South Asian; and 1,124 were South Asians but did not have any persons in the household who met the age criterion. Among the eligible participants identifi ed, 220 completed the telephone survey, representing a response rate of 66.9 per cent, a higher than average response rate in many telephone surveys with older adults (Ford, Havstad, Hill, & Kart, 2000 ;McFall & Yerkes, 1998 ).…”
Section: Methodsmentioning
confidence: 99%